Understanding regular expressions : identifying, verifying, and manipulating text data efficiently and easily (O'Reilly, 2017)
"The regular expression (regex) has been around for over 60 years and it's still poorly understood--and incorrectly used--by most developers. Why? Mainly because regexes are rarely taught to developers; they're just left to "pick them up" as they go along. This means most developers don't know what regexes do, how they work, how to use them, how to optimize them, or how to maintain them. In this course, regex expert Damian Conway changes this equation. He explains regexes in detail and shows you the power of these amazing and efficient tools."--Resource description page